PENGELOLAAN HUBUNGAN INTERPERSONAL PASANGAN SUAMI-ISTRI MENIKAH USIA DINI - Febriyanti, RT Annisa; Naryoso, Agus; Noor Rakhmad, Wiwid (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
This research is motivated by the communication problems arising from early marriage. Ideally, marriage involves nurturing relationships but contrary to this ideal, conflicts often arise due to low communication quality among early-married couples. This study aims to describe the process of managing interpersonal relationships in early-married couples. The theories used in this research are Conflict Management and Relationship Maintenance Theory. The research method employed is descriptive-qualitative, using data collection techniques through deep interviews. The research findings explain the decisions to marry early, which can be caused by factors such as Marriage By Accident, education, and arranged marriages. Relationship management involves providing affection, such as openness, attention, support, and love. Couples adjust their communication by processes of mutual understanding and openness with each other. Moreover, they adjust by setting aside their egos to prioritize family needs over personal ones. Relationship management is facilitated by openness; some early-married couples are open, while others have one open partner who is open and one who is closed, or both partners may be closed. Additionally, early-married couples may lack specific rules but often have agreements regarding task division Communication to address issues in early marriage often involves discussions and negotiations between the spouses. While increasing quality time together is often cited as the most effective form of relationship management, in reality, most couples spend more time with their friends. Early-married couples try to set boundaries with their families and others to prevent interference. Conflict communication involves conflict management strategies such as win-lose strategies, verbal aggressiveness strategies, active fighting strategies, force strategies, and talk strategies. In conclusion, managing relationships in early marriage requires intensive and open communication. Additionally, it requires expressions of affection, relationship boundaries, openness, discussion, quality time, and efforts to resolve conflicts.